Tumor microenvironment: Challenges and opportunities in targeting metastasis of triple negative breast cancer - Deepak, K.G.K.; Vempati, Rahul; Nagaraju, Ganji Purnachandra; Dasari, Venkata Ramesh; S., Nagini; Rao, D.N.; Malla, Rama Rao (Pharmacological research, 2020)
[Display omitted] •TNBC is highly challenging subtype of breast cancer due to unique tumor microenvironment (TME).•TME associates with aggressive nature, metastasis and drug resistance in TNBC.•Epigenetic based regulations within TME drive carcinogenesis.•Novel therapeutic targets of TME helps in early diagnosis and effective treatment of TNBC. Triple negative breast cancer (TNBC) is most aggressive subtype of breast cancers with high probability of metastasis as well as lack of specific targets and targeted therapeutics. TNBC is characterized with unique tumor microenvironment (TME), which differs from other subtypes. TME is associated with induction of proliferation, angiogenesis, inhibition of apoptosis and immune system suppression, and drug resistance. Exosomes are promising nanovesicles, which orchestrate the TME by communicating with different cells within TME. The components of TME including transformed ECM, soluble factors, immune suppressive cells, epigenetic modifications and re-programmed fibroblasts together hamper antitumor response and helps progression and metastasis of TNBCs. Therefore, TME could be a therapeutic target of TNBC. The current review presents latest updates on the role of exosomes in modulation of TME, approaches for targeting TME and combination of immune checkpoint inhibitors and target chemotherapeutics. Finally, we also discussed various phytochemicals that alter genetic, transcriptomic and proteomic profiles of TME along with current challenges and future implications. Thus, as TME is associated with the hallmarks of TNBC, the understanding of the impact of different components can improve the clinical benefits of TNBC patients.